Analysis of SDI Strategies, Water Use, Water Productivity, Corn Yield, and Soil Water Model - Rocio Reyes Esteves (Kansas Agricultural Experiment Station Research Reports, 2024)
Declining groundwater in the Central Great Plains is pressing producers to look for more efficient irrigation methods than the traditional center‐pivot sprinkler and linear systems. Subsurface drip irrigation (SDI) can be a viable alternative when water is limited, or irrigation capacity is insufficient in conventional methods. However, the irrigation system does not guarantee all the potential benefits; adequate design and management are also required. The research was conducted at Kansas State University Northwest Research and Extension Center in Colby, KS, during the 2023 growing season to evaluate irrigation strategies, water use, water productivity, and corn yield as well as to simulate and calibrate the soil water redistribution model. Irrigation strategies were combinations of irrigation frequency/timing (weekly or bi-weekly) applied pre- and post-silking. Irrigation levels were 100%, 85%, 75%, and 65% of calculated well-watered ET minus rain. Average irrigation amounts ranged from 6.9 to 11.2 inches. Hybrid maturity was 112 days, planted at 28,000 seeds/a. Corn yields were slightly affected by irrigation strategies, ranging from 195.8 to 202.3 bu/a.
Keywords: corn; subsurface drip irrigation; yield; water productivity; soil water modeling